Improving the Performance of Palladium-Catalyzed Telomerization of 1,3-Butadiene with Malonate by Alcohol Solvent - Chen, Xuan; Shen, Chaoren; Dong, Kaiwu (Synlett, 2025)
Using alcohol instead of largely excessive malonate as the solvent can improve the performance of palladium-catalyzed telomerization of 1,3-butadiene with malonate. Under the basic conditions, the main reaction was not overwhelmed by the telomerization of 1,3-butadiene with methanol solvent. With this method, methyl (E)-deca-4,9-dienoate, the intermediate for the synthesis of 10-hydroxy decanoic acid, undecanedioic acid, and 11-hydroxy undecanoic acid, can be prepared from the telomerization of 1,3-butadiene with dimethyl malonate in good yield.
Keywords: telomerization; 1,3-butadiene; malonate; solvent; palladium